Analysis of quality education for polytechnic graduate : a survey in Malaysia - Faridah binti Suboh (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
The purpose of this study is to identify the application of quality knowledge in industries. Second purpose is to evaluate the need on quality knowledge for polytechnic graduate and the industry and thirdly, to evaluate the needs of soft skills knowledge for polytechnic graduate. The scope of study limited to the polytechnic graduate from the Mechanical and Electrical Department. One hundred (100) set of questionnaires were distributed to the Mechanical and Electrical Department graduates. However, only 70 questionnaires were returned (70% response rate). The reliability value (alpha cronbach) of the instrument was 0.833. Data collected were analyzed using Statistical Package for the Social Science software (SPSS/PC+) version 15 to find the mean and frequency by using descriptive statistics. Pearson correlation, t-test and ANOVA are used to analyze the inferential statistics. The descriptive results shows that the need of quality knowledge in workplace is high (mean = 4.12). While the need of soft skill shows that mean 4.15 were also high and the mean of quality assurance is 4.16 The results of the hypothesis shows that there is no significant differences between quality assurance, quality knowledge need, and soft skill knowledge need with existing position by using ANOVA (p>0.05). The result also shows that there is no significant relationship between quality assurance, quality knowledge need, and soft skill knowledge need with students CGPA (p>0.05). As for the t-test quality assurance, quality knowledge need, and soft skill knowledge need with student qualification, it shows that there is no significant differences.